AVALIAÇÃO IN VITRO DE NANOPARTÍCULAS DE ZEÍNA, CASEÍNA E ALBUMINA - Barbieri, Marcio (2019)
In recent decades, pharmaceutical technology has sought strategies to develop innovative drug delivery systems aimed at improving therapeutic value, mainly considering the reduction of toxicity and increased bioavailability of various compounds used in the medical clinic. The development of nanostructured systems has interesting physicochemical properties, such as protection of the encapsulated drug and progressive and controlled release of the compound. The evaluation of biologically loaded nanoparticles (NPs) involves the evaluation of assays, for example, antioxidants, antifungal, cytotoxic on normal and tumor lineages, in addition to other analyzes. Antioxidant, antifungal and cytotoxic assays are performed in nanostructured systems, due to the various formulations obtained, for example, using natural products and drugs such as amphotericin B and voriconazole, respectively. Also, this same rationale is valid for antitumor drugs, which are advocated as interesting compounds for encapsulation in nanoparticles, due to their toxicity on normal cells and limited routes of administration. However, because these assays are under the influence not only of the compounds of interest, in the case of antioxidants, antitumor and antifungals, but also of the polymers composing the system, it is important to evaluate the effect of the empty nanoparticles. Thus, this work aimed at the development of NPs of albumin (BSA), casein (CSNA) and zein (ZNA), in order to verify its possible effects on antioxidant, antifungal and cytotoxic systems. The albumin nanoparticles (NPS-BSA) and casein (NPS-CSNA) were developed by the coacervation technique and zein nanoparticles (NPS-ZNA) by the liquid-liquid dispersion method. The NPS-BSA obtained had a mean diameter of 358 ± 24 nm, polydispersity index 0.202 ± 0.078, zeta potential -14.6 ± 1.97, NPS-CSNA mean diameter 333.4 ± 26.3 nm, polydispersity index 0.280 ± 0.03, zeta potential -17.7 ± 1.04, and NPS-ZNA had mean diameter 197.7 ± 2.9 nm, polydispersion index 0.173 ± 0.07 and zeta potential -32.5 ± 4.28. The morphological analysis revealed that the NPS-BSA, NPS-CSNA and NPS-ZNA nanoparticles have a spherical and smooth shape. The applicability of NPs was evaluated against the antioxidant potential of 2,2'-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazila (DPPH) and hypochlorous acid (HOCl). The results of the antioxidant activity of NPS-BSA, NPS-CSNA and NPS-ZNA show sequestering ability on ABTS • + and HOCl radical, but not on the DPPH radical. The antifungal study showed that NPS-ZNA has an effect on colony-forming unit growth, exhibiting superior activity when compared to NPS-BSA and NPS-CSNA. The cytotoxic assay on Hep2 cells showed that only NPS-ZNA exerted significant activity on this system. In this way, it can be concluded that the NPS-BSA, NPS-CSNA and NPS-ZNA obtained an adequate physical-chemical profile, with the possibility of carrying, with low interference between polymer and possible encapsulated compound, and that exert influence in the tests antioxidants, antifungal and cytotoxicity, depending on the nanoparticles used and their concentration, demonstrating the importance of the analysis of empty nanostructured systems in biological assays.